Evaluation of enterprise survival: case of Latvian enterprises - Scacun, Natalia; Voronova, Irina (Business, Management and Economics Engineering, 2018)
Authors study the nature of insolvency both from the legal point of view and scientist position as well as updating tendencies of an insolvency of enterprises in recent years. The subject of the study has been selected company’s survival potential that is analyzed with financial ratio analysis using bankruptcy prediction models. Considering research results, authors identify models that are applicable to a particular industry. Authors put primary metal industry (NACE 24) for the study. The aim of the paper is to investigate the survival potential of enterprises by testing existing parametric models of insolvency forecasting and assessing their potential for use in the economic conditions of Latvia. During the investigation has been reviewed the concept of the financially healthy company and its relation with the main success development factors.